Near Real-Time Petrologic Monitoring on Volcanic Glass to Infer Magmatic Processes During the February–April 2021 Paroxysms of the South-East Crater, Etna - Corsaro, Rosa Anna; Miraglia, Lucia (Frontiers in Earth Science, 2022)
The South-East crater of Etna (SEC) is the most active summit crater over the last 20 years, producing lava fountains in 2000, 2007-08, 2011-14, which have been monitored by the INGV Etna Observatory. The syn-eruptive petrologic monitoring comprises sample collections, archiving, preparation for analyses, analyses of glass compositions with SEM-EDS and data interpretation. This procedure is generally carried out within 24 hours from the moment the sample was erupted, to detect possible changes of magma composition during the ongoing activity. This paper presents the variation of volcanic glass compositions during the paroxysmal activity of the SEC, which began in December 2020 and climaxed with 17 episodes from 16 February to 1 April 2021. The temporal trends of compositional parameters allowed us to hypothesize the pre-eruptive magmatic processes (e.g. fractional crystallization and mixing) that caused the compositional variations; correlation between magma dynamics and volcanological characteristics of the paroxysms requires future studies.